Fundamentalisms and society : reclaiming the sciences, the family, and education - Marty, Martin E., 1928-; Appleby, R. Scott, 1956-; American Academy of Arts and Sciences (Chicago : University of Chicago Press, 1993)
This book, the second volume of the Fundamentalism Project, provides a systematic overview of the advances made by antisecular religious movements over the past twenty-five years and shows the impact these movements have had on human relations, education, women's rights, and scientific research. The essays consider developments within the religious traditions of Islam, Judaism, Christianity, Buddhism, and Hinduism in over a dozen nations. What do individual fundamentalist movements regard as the foundations for and limits of knowledge? What do they understand the proper role of science to be? And how do their world views determine the application of technology? The distinguished contributors to this volume - anthropologists, historians of religion, historians of science, and sociologists - address these and other questions through a discussion of topics such as educational structures of Hindu revivalism, women in fundamentalist Iran and Pakistan, and the creationist cosmos of Protestant fundamentalism. In a concluding essay, William H. McNeill situates contemporary fundamentalisms within a world historical context. The Fundamentalism Project is a monumental undertaking by the American Academy of Arts and Sciences that involves an international group of scholars. Taken together, the volumes in this series will become a standard reference for educators and policy analysts for years to come.
pt. 3. Education and media: Fundamentalist impact on education and the media : an overview / Majid Tehranian -- Islamic fundamentalism in Iran and the discourse of development / Majid Tehranian -- Jewish fundamentalism in Israeli education / Michael Rosenak -- The evangelical awakening in Guatemala : fundamentalism and education in the United States / Susan Rose and Quentin Schultz -- Christian fundamentalism and education in the United States / Susan Rose -- The two faces of fundamentalist higher education / Quentin Schultze -- Hindu revivalism and education in north-central India / Krishna Kumar -- Fundamentalism and the world of the 1990s / William H. McNeill.
"Sponsored by the American Academy of Arts and Sciences."
Includes bibliographical references and index.
Sponsored by the American Academy of Arts and Sciences.
Keywords: Religious fundamentalism; Religion and sociology